Influencing Factors of Repurchase Intention on Online Food Delivery Service in Indonesia - Kezia Christine; Margaretha Pink Berlianto (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The purpose of this study was to determine the factors that influence repurchase intentions at online food delivery services in Indonesia. This study uses a quantitative study method with a cross-sectional approach with purposive sampling as the sampling technique. The sample of this research is ShopeeFood users who live in Greater Jakarta and are less than 40 years old. This study found that several factors influence repurchase intentions at Shopee Food, such as performance expectancy, habit, impulsive buying tendency, and openness to novelty. Impulse buying tendency was the most substantial factor influencing repurchase intention. Furthermore, congruity to self-image is not proven to have a significant positive effect on repurchase intention. This research only focuses on how certain factors influence the repurchase intention of Generation Y and Z OFDS consumers. So further research is needed to examine other internal and external factors. This research provides information on ShopeeFood management in making managerial decisions.